Hybrid PET/MRI-based delineation of gross tumor volume in head and neck cancer and tumor parameter analysis. Issue 7 (July 2017) - Ma, Jie-Tao; Han, Cheng-Bo; Zheng, Jia-He; Sun, Hong-Zan; Zhang, Shao-Min; Xin, Jun; Guo, Qi-Yong
Abstract : Objectives: Accurate target delineation allows an increase in radiation dose to the target tumor while reducing damage to the surrounding normal tissue. However, there is currently no standard for evaluating volumes measured by different imaging modalities. The aim of this study is to evaluate the feasibility of contouring gross tumor volume (GTV) by PET/MRI in head and neck cancer, and to define an adaptive threshold level (aTL) for delineating the biological target volume (BTV). Patients and methods: Eighteen head and neck cancer patients underwent time of flight PET/MRI before chemoradiotherapy. Different GTVs of primary tumors and metastatic lymph nodes were manually contoured on MRI (GTVMRI ), PET (GTVVIS ), and fused PET/MRI (GTVFUS ). An MRI-based GTV contour was substituted for the pathologic GTV. The percentile threshold boundary of the maximum standardized uptake value (SUVmax ) for the BTV was determined when the volume of BTV approached that of GTVMRI . Results: All GTVs were highly correlated (all Pearson's r >0.85, all P <0.001). Tumor diameter strongly correlated with GTVs ( r =0.7–0.8 for all lesions and primary tumor; r =0.8–0.9 for lymph node metastases). aTL and SUVmax were moderately correlated for all lesions ( r =−0.692, P <0.001) and were strongly correlated for primary tumors ( r =−0.866, P <0.001). Conclusion: Delineating GTV on hybrid PET/MRIs is feasible, and aTL, the threshold boundary of BTV, was correlated inversely with the SUVmax . Abstract : Supplemental Digital Content is available in the text.